Review Of Religious Cultural Education Model In Achieving Sustainable Development Goals In The Education Sector Number 4 Through Theoretical Approach - Warjo Warjo; M. Luthfi Abdullah; Eliyawati Eliyawati (STAI Miftahul Ula Nganjuk, 2020)
The SDGs have the main principle, namely that they are universally applicable, with the development target applicable to all underdeveloped, developing, and developed areas, as well as every citizen. The Sustainable Development Goals (SDGs) in the field of education are related to the quality of good education with the substance of ensuring the distribution of quality education and increasing learning opportunities for all, ensuring inclusive and equitable education, and encouraging lifelong learning opportunities for all. Quality education, in accordance with the mandate in the law, is more emphasized in character building. This article is a conceptual overview of finding a character education model that is accessible to all levels of society and provides lifelong learning opportunities for all. In looking for answers to these objectives, the author uses a qualitative approach by analyzing the literature related to existing problems. The results obtained from this study are in the form of a religious culture-based education model. There are at least five religious cultures that can be applied, namely; (1) TSP (Tahan dari buang sampah sembarangan, Simpan sampah pada tempatnya, Pungut sampah insya Allah sedekah); (2) BEBASKOMIBA (BE-berantakan-rapikan; BAS-basah-keringkan; KO-kotor-bersihkan; MI-miring-luruskan; BA-bahaya-amankan); (3) 3M (Mulai dari diri sendiri; Mulai dari hal yang kecil; Mulai saat ini); (4) 5K (Kerja keras; Kerja cerdas; Kerja mawas; Kerja tuntas; Kerka ikhlas); dan (5) 7B (Beribadah dengan baik, benar, dan istiqomah; Berakhlak baik; Belajar tekun tiada henti; Bekerja keras, cerdas, dan ikhlas; Bersahaja dalam hidup; Bantu sesama; Bersihkan hati selalu). Based on the study of the author, this educational model can be applied to achieve SDGs in education number 4Religious Cultural Education Model